2015
DOI: 10.15640/jgpc.v3n2a4
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Influence of Ubuntu Principle on the South Africa Peace Building Process

Abstract: Sustainable peace building demands that we move beyond the spirit of revenge and to open our world-view to include others. This paper explores how Ubuntu, a South African tacit principle helps in the peace building process in South Africa. It also examines how Ubuntu is essential for unity of humanity and emphasizes the importance of constantly referring to the principles of empathy, forgiveness, sharing in a conscious effort to resolving common problems. The discussion critiqued the western approach to peace … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…According to Ubuntu, this challenge demonstrates that people must work together as one, irrespective of their differences and diversities. This is in line with the assumption of Arthur, Issifu and Marfo (2015) who claimed that Ubuntu is a strategy that ensures unity among the people despite their diversities. Yet, the analysis also indicated that the students were able to accommodate and listen to themselves, and show compassion to those who, one way or the other were unable to meet up with their schedules.…”
Section: Struggle To Locate Group Memberssupporting
confidence: 86%
See 1 more Smart Citation
“…According to Ubuntu, this challenge demonstrates that people must work together as one, irrespective of their differences and diversities. This is in line with the assumption of Arthur, Issifu and Marfo (2015) who claimed that Ubuntu is a strategy that ensures unity among the people despite their diversities. Yet, the analysis also indicated that the students were able to accommodate and listen to themselves, and show compassion to those who, one way or the other were unable to meet up with their schedules.…”
Section: Struggle To Locate Group Memberssupporting
confidence: 86%
“…However, the bottom line still bothers on unity and togetherness of humanity among the people. In the position of Arthur, Issifu and Marfo (2015), Ubuntu is a strategy that ensures unity among the people despite their diversities. It is also approached as an established, indigenous way of managing people (Swanson, 2008).…”
Section: Situating Ubuntu As a Theoretical Frameworkmentioning
confidence: 99%
“…This framework has also been suggested for such purposes by Bongmba who suggested that given the divisions on same-sex relationships in Africa, 'the notion of Ubuntu offers a way of rethinking the negative discourses on same-sex relationships in Africa and in the African church' (Bongmba 2016:15). Ubuntu concept was also employed by the Truth and Reconciliation Commission of South Africa, and its largely positive results are well documented (Arthur, Issifu & Marfo 2015).…”
Section: Ubuntumentioning
confidence: 99%
“…Ubuntu, as African philosophy, over the years, has been used as a synonym to the African way of life, which in the coinage of Mokgoro (1998), Omodan and Dube (2020) is Africanism. This philosophy originated within ancient Africa communities/villages where diverse human beings lived together in harmony, for the greater benefit of society despite their diversities (Omodan, 2019), and from African idioms such as 'Motho ke motho ka batho' and 'Umuntu ngumuntu ngabantu' which means "a person is a person through others" and "I am because we are" (Ramose, 1999;Goduka, 2000;Lefa, 2015;Arthur, Issifu & Marfo, 2015). Arthur et al (2015) further contemplate the concept of Ubuntu by linking it to the way of ensuring unity among people in the rural setting, that is, Ubuntu is linked to indigenous ways of managing or resolving conflicts within and among people (Swanson, 2008).…”
Section: Theorising Ubuntu As a Tool To Decolonising Students' Unrestmentioning
confidence: 99%